(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
In the era of Global changes, it is necessary to protect young people from destructive attacks of destructive ideas and destructive ideologies, to comprehensively study their features. In this case, the National idea serves as a nationwide program. After all, in the era of global changes, it is necessary to instill a national idea in the minds, hearts and inner world of young people on the basis of the programmatic idea “from national revival – towards national rise”, to educate them in the spirit of devotion to the native land, to further form initiative, dedication, moral qualities in them – to become an extremely honorable task. Only then will we achieve in perspective the upbringing of a spiritually harmonious person, a healthy generation.